Germinación de Leucanthemum maestracense y L. gracilicaule, Compositae - Escribá, Mari Carmen; Laguna, Emilio (Botanica Complutensis, 2007)
We have studied the germination of Leucanthemum maestracense Vogt & Hellwig and L. gracilicaule (Dufour) Pau. Two hemicriptophyt of big ornamental valour, they are considered by UICN as LRlc. Seeds were positive germinated best at Leucanthemum maestracense.